Pengaruh Rata-Rata Lama Sekolah dan Tingkat Pengangguran Terbuka terhadap Tingkat Kemiskinan di Kabupaten Brebes Tahun 2014–2024 - Mahendra Arya Wisnu Pradana; Muhammad Sabandi; Dewi Kusuma Wardani (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Poverty remains a structural challenge in Brebes Regency despite improvements in several socio-economic indicators, while empirical evidence on the roles of education and unemployment in shaping poverty at the local level remains mixed. This study aims to examine the effects of average years of schooling and the open unemployment rate on poverty levels in Brebes Regency during the 2014–2024 period. Using a quantitative approach, this study employs multiple linear regression analysis based on time-series data obtained from official publications of Statistics Indonesia. The results indicate that average years of schooling have a significant and negative effect on poverty levels, suggesting that improvements in educational attainment contribute to poverty reduction, whereas the open unemployment rate does not show a statistically significant effect despite exhibiting a positive relationship. Simultaneously, both variables explain a substantial proportion of the variation in poverty levels over the study period, highlighting the more consistent role of education compared to unemployment in explaining poverty dynamics in Brebes Regency. The study concludes that poverty alleviation policies should prioritize improving access to and the quality of education, particularly at the primary and secondary levels, while policy implications and future research directions emphasize the need to incorporate informal employment and other structural factors to achieve a more comprehensive understanding of poverty.